Notch Signaling in Sertoli Cells Regulates Cyclical Gene Expression of Hes1 but Is Dispensable for Mouse Spermatogenesis - Hasegawa, Kazuteru (American Society for Microbiology, 2012)
Mammalian spermatogenesis is a highly regulated system dedicated to the continuous production of spermatozoa from spermatogonial stem cells, and the process largely depends on microenvironments created by Sertoli cells, unique somatic cells that reside within a seminiferous tubule. Spermatogenesis progresses with a cyclical program known as the “seminiferous epithelial cycle,” which is accompanied with cyclical gene expression changes in Sertoli cells. However, it is unclear how the cyclicity in Sertoli cells is regulated. Here, we report that Notch signaling, which is known to play an important role for germ cell development in Drosophila and Caenorhabditis elegans, is cyclically activated in Sertoli cells and regulates stage-dependent gene expression of Hes1. To elucidate the regulatory mechanism of stage-dependent Hes1 expression and the role of Notch signaling in mouse spermatogenesis, we inactivated Notch signaling in Sertoli cells by deleting protein O-fucosyltransferase 1 (Pofut1), using the cre-loxP system, and found that stage-dependent Hes1 expression was dependent on the activation of Notch signaling. Unexpectedly, however, spermatogenesis proceeded normally. Our results thus indicate that Notch signaling regulates cyclical gene expression in Sertoli cells but is dispensable for mouse spermatogenesis. This highlights the evolutionary divergences in regulation of germ cell development.